Assessment of right ventricular systolic function in children with repaired tetralogy of Fallot by multiple‐view from single acoustic window with speckle tracking echocardiography. - Bao, Sheng‐Fang; Zhang, Yu‐Qi; Chen, Li‐Jun; Zhong, Yu‐Min; Wang, Qian; Zhang, Zhi‐Fang (Echocardiography, 2019)
Background: Challenges remain in quantitative evaluation of right ventricular (RV) function by echocardiography. Multiple‐view assessment is believed to provide a more comprehensive quantification of RV function than conventional single‐view analysis. Peak systolic longitudinal RV strain (RVLS) measured by speckle tracking echocardiography (STE) has clinical and prognostic value. No study has investigated RV systolic function in the repaired tetralogy of Fallot (rTOF) using a standardized four‐view iRotate model from one apical view. Herein, we examined the feasibility and accuracy of the four‐view analysis from apical window in quantitation of RVLS among children with rTOF. Methods: Thirty‐seven children with rTOF and 37 age‐ and gender‐matched controls were prospectively enrolled. Tricuspid annular plane systolic excursion (TAPSE) and tricuspid annular peak systolic velocity (TDI‐S′) and fractional area change(FAC) were obtained. RVLS of four free‐walls were analyzed by dedicated RV speckle tracking software. Echocardiographic parameters were compared with the right ventricular ejection fraction (RVEF) measured by the cardiac magnetic resonance (CMR) in children with rTOF. Results: Multi‐view RVLS analysis from apical window was feasible in 35 children with rTOF and all the controls. Compared with age‐ and gender‐matched controls, RVLS of the anterior, lateral, inferior‐a, and inferior‐b walls were significantly reduced in children with rTOF (P < 0.001). RVLS of the anterior, lateral, inferior‐a, and inferior‐b walls correlated well with CMR‐RVEF in children with rTOF (r = −0.667, −0.743, −0.808, −0.695, P < 0.001). Conclusions: Multi‐view analysis of RVLS from apical window can be applied to evaluate the RV function in children with rTOF. RVLS of the inferior wall‐a in the aortic view is a novel and accurate indicator of RV function because of its good reproducibility and strong correlation with CMR‐RVEF.